Factors associated with quality of life in patients with Chagas disease: SaMi-Trop project. - Nayara Dornela Quintino; Ester Cerdeira Sabino; José Luiz Padilha da Silva; Antonio Luiz Pinho Ribeiro; Ariela Mota Ferreira; Gabriela Lemes Davi; Claudia Di Lorenzo Oliveira; Clareci Silva Cardoso (PLoS Neglected Tropical Diseases)
Trial registration NCT02646943.